2018
DOI: 10.4103/ijps.ijps_209_17
|View full text |Cite
|
Sign up to set email alerts
|

Scalp expansion: Surgical considerations and possible future directions

Abstract: Introduction:Repairing large scalp defects has always been a difficult task for plastic surgeons. This is because the requirements of such procedures are two-fold: sufficient soft-tissue coverage is required, and to obtain a satisfactory aesthetic outcome, a sufficient number of covering hairs should be ideally provided.Materials and Methods:Based on the author's experience in this repair technique over a 20-year period, this article presents some technical details of scalp expansion, surgical refinements and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…During the expansion process, the epidermis exhibits increasing mitotic activity, and the dermis thins significantly, which is frequently masked by the thick fibrous capsule formation all around the expander, resulting in limitation in flap mobility during the reconstruction process. [22][23][24] Therefore, the multidirectional relaxing incision during scalp wound closure provides improved flap mobility, resulting in a decreased risk of wound margin tension and dehiscence. 23,[25][26][27] According to Bilkay et al, 28 there was no need for capsule excision, but only scoring with great attention, to release the tightness without affecting the blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…During the expansion process, the epidermis exhibits increasing mitotic activity, and the dermis thins significantly, which is frequently masked by the thick fibrous capsule formation all around the expander, resulting in limitation in flap mobility during the reconstruction process. [22][23][24] Therefore, the multidirectional relaxing incision during scalp wound closure provides improved flap mobility, resulting in a decreased risk of wound margin tension and dehiscence. 23,[25][26][27] According to Bilkay et al, 28 there was no need for capsule excision, but only scoring with great attention, to release the tightness without affecting the blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…However, clear-of-tumor defect margins are mandatory because of their movement from the original position. An alternative, not present in our review, may be represented by a primary reconstruction with skin grafting followed by delayed, subgaleal 34 or external, 35 scalp expansion in case of wide defects or necessity to wait for safe monitoring. Local flaps, in fact, are successfully employed in small (<50 cm 2 ) defects, 12 , 16 , 24 , 25 , 27 whereas they need association with skin grafts in case of wider wounds.…”
Section: Discussionmentioning
confidence: 99%
“…As regard flap loss, seven studies showing partial flap loss with total event rate 9.010 with insignificant heterogeneity between studies as shown in table [4]; eight studies showing total graft loss with total event rate 7.323 with significant heterogeneity between studies table [5], and two studies showing donor site morbidity with total event rate 19.869 with significant heterogeneity between studies as shown in figures [3]; five studies showing Revision surgery with total event rate 16.128 with insignificant heterogeneity between studies as shown in table [6].…”
Section: Meta-analysismentioning
confidence: 99%
“…Several variants exist, including the temporoparietal fascia flap [5] , 5. Tissue expander: Patients with post-surgical scalp baldness should seriously consider this surgery [6] , 6. Drilling of the diplopic space and skin grafting: The outer table of the skull can be drilled to access the diplopic area.…”
Section: Introductionmentioning
confidence: 99%